Antispasmodic, antidepressant and anxiolytic effects of extracts from Schinus lentiscifolius Marchand leaves - Vanegas Andrade, Catalina (2022)
Schinus lentiscifolius (Anacardiaceae) is widely used in folk medicine for treating gastrointestinal and emotional complaints but there are no scientific studies that support these uses. This work aims at evaluating the antispasmodic and central effects of S. lentiscifolius as well as the flavonoids presence in the tincture (SchT) and the composition of the essential oil (SchO). SchT inhibited the concentrationresponse curves (CRC) of carbachol and calcium in a non-competitive way in isolated rat intestine, bladder and uterus. SchT also non-competitively inhibited the CRC of histamine in guinea-pig intestine and the CRCs of serotonin and oxytocin in rat uterus. Isoquercetin and rutin were identified in SchT. The behavioral effects of SchT, SchO and infusion of S. lentiscifolius leaves (SchW) were tested in mice. These extracts showed an anxiolytic-like effect in the novelty-suppressed feeding test, which was reversed by flumazenil except in SchO-treated mice. Only SchO reduced the spontaneous locomotor function in the open field test. Also, SchT and SchW decreased immobility time in both, the tail suspension (TST) and forced swimming tests, while SchO produced the same effect in the TST. D-limonene and a-santalol were the main components found in SchO. The results demonstrated that extracts obtained from S. lentiscifolius leaves were effective as intestinal, urinary and uterine antispasmodics. SchT and SchW exhibited anxiolytic and antidepressant properties without sedation, whereas SchO showed also sedative properties. Therefore, the present study gives preclinical support to the traditional use of this plant for gastrointestinal and depressive or emotional symptoms.